Efektivitas Pengobatan Topikal pada Pitiriasis Versikolor - Pusung, Andreas V.; Suling, Pieter L.; Niode, Nurdjannah J. (Universitas Sam Ratulangi, 2021)
Abstract: Pityriasis versicolor is a chronic mild superficial fungal infection of the skin due to lipophilic fungi Malassezia. It commonly affects the face, neck, abdomen, proximal extremities, axilla, groin, and genitalia. The occurrence of this disease is not influenced by sex, albeit, age influences its incidence since it is more common in adolescents and young adults.Therefore, an effective, safe, and affordable treatment should be considered. The first-line therapy for pity-riasis versicolor is topical treatment, classified into specific and non-specific antifungal agents. This study was aimed to determine the efficacy of topical treatment in pityriasis versicolor. This was a literature review study using three databases, namely PubMed, ClinicalKey, and Google Scholar and the keywords of